Analisis Digitalisasi Pelayanan Pembayaran Pensiun Melalui Aplikasi Taspen Otentikasi Di PT. Taspen (Persero) Kantor Cabang Utama Medan - Retno Sri Rindi Yani; Muhammad Arif; Riska Wulandari Sitorus (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
The role of PT. TASPEN in serving the authentication application system for pension fund recipients in Medan City is very important, this is because in its implementation there are still several problems that become obstacles, namely related to human resources (HR) who have difficulty using the authentication application due to age and the lack of application system servers. so that when used simultaneously errors often occur. This research aims to analyze and describe how the process of digitizing pension payment services through the Taspen Authentication application at PT. Taspen (Persero) KCU Medan and the obstacles that occur in servicing the application. The method used in this research is qualitative with a descriptive approach. This research uses role theory, e-government, and public policy. Research data was obtained from literature and previous research. The results of this research show that PT. TASPEN plays a very important role in serving the pension fund authentication application system and that PT. TASPEN's role is very effective in implementing the Taspen authentication application system. It's just that there are several obstacles, namely the human resources (HR) of retired participants as application users who have difficulty using the application due to age and lack of evaluation in handling obstacles that are often encountered due to the use of authentication applications such as application system errors occurring when used simultaneously.